2009
DOI: 10.1002/tea.20283
|View full text |Cite
|
Sign up to set email alerts
|

Does teaching experience matter? Examining biology teachers' prior knowledge for teaching in an alternative certification program

Abstract: Alternative certification programs (ACPs) have been proposed as a viable way to address teacher shortages, yet we know little about how teacher knowledge develops within such programs. The purpose of this study was to investigate prior knowledge for teaching among students entering an ACP, comparing individuals with teaching experience to those lacking teaching experience. Of the four participants seeking secondary biology teaching certification, two participants had 2 years of prior biology teaching experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
166
3
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(208 citation statements)
references
References 62 publications
14
166
3
16
Order By: Relevance
“…The interaction of the components of PCK has been noted to be limited in research with novice teachers (González and Rossi, 2014a); a similar situation has been demonstrated in investigations with preservice teachers (Friedrichsen et al 2009). Kind (2009) points that PCK remains unnoticed by many science teachers; for instance, as many of our fellow university teachers, Sylvia and Juliette, the two experienced teachers in the present work had never heard the term.…”
Section: Discussionmentioning
confidence: 88%
“…The interaction of the components of PCK has been noted to be limited in research with novice teachers (González and Rossi, 2014a); a similar situation has been demonstrated in investigations with preservice teachers (Friedrichsen et al 2009). Kind (2009) points that PCK remains unnoticed by many science teachers; for instance, as many of our fellow university teachers, Sylvia and Juliette, the two experienced teachers in the present work had never heard the term.…”
Section: Discussionmentioning
confidence: 88%
“…In this sense it is considered to be subject specific (E. A. Davis & Krajcik, 2005;Friedrichsen, et al, 2009). In times of a curricular reform, teachers have to bring their PCK in line with the reform demands.…”
Section: Pedagogical Content Knowledge (Pck)mentioning
confidence: 99%
“…Friedrichsen et al (2009) consideran tres aspectos: los propios antecedentes escolares, la formación inicial y la experiencia profesional. Dado que la literatura ha puesto de manifiesto que organizar al profesorado en función de su conocimiento profesional docente ayuda a formular propuestas de mejora de la formación (Van Driel y Berry, 2012;Nilsson y Vikström, 2015), nosotros añadimos a los tres aspectos anteriores: i) la formación continua recibida durante la trayectoria profesional; ii) el conocimiento de los resultados obtenidos por la investigación, adquirido mediante la lectura de revistas o a través de cursos, y iii) la realización de investigaciones o innovaciones que permitan apreciar la eficacia de las nuevas propuestas de enseñanza-aprendizaje.…”
Section: Enseñanza De Las Ciencias Núm 361 (2018): 25-44unclassified